THORAX MULTI-SLICE COMPUTER TOMOGRAPHY (MSCT) EXAMINATION TECHNIQUE IN THE CASE OF MEDIASTINUM TUMOR AT RADIOLOGY INSTALATION OF SEMARANG DISTRICT GENERAL HOSPITAL - Mayasari, Ike; Sukmaningtyas, Hermina; Wibowo, Ardi Soesilo; Santjaka, Aris; Anwar, M. Choerul; Latifah, Leny (Proceedings of the International Conference on Applied Science and Health, 2017)
Background: Thorax Multi-slice computer tomography (MSCT) scan examination requires contrast medium to image the difference in density with the surrounding tissue. The contrast images is largely determined by the volume of contrast, injection rate and injection methods. Thorax CT scan is performed by slice thickness of 5-10 mm. Meanwhile, it should use the routine slice thickness of 10 mm. Slice thickness of 8-10 mm of coronal and sagittal images require reconstruction by thin slices of 1-1.5 mm and subsequently by applying 3D. Aims: This is to analyse the volume of contrast and slice thickness used in the examination of tumor mediastinum by thorax MSCT examination. Methods: This research used descriptive qualitative design with case study approach, described and explained systematically, related to the procedure of Thorax MSCT examination technique in the case of mediastinum tumor with 3 samples of 3 patient and assessment performed by three radiologist as respondents. Results: This study indicates the success of the use of proper contrast of 80 cc and slice thickness of 2-3 mm to observe lesions of mediastinal tumor. Conclusion: Thorax MSCT examination in the case of mediastinum tumor should use contrast 80 cc and slice thickness of 2-3 mm to observe lesions of mediastinal tumor and coronal and sagittal axial slices, because the sagittal slice can show the lymphadenopathy enlargement so that the mediastinum tumor is clearly visible. The print out or filming results should be included the MPR or 3D to show the presence or absence of bone destruction and metastases.Â